Analisis SWOT dalam Menentukan Strategi Implementasi E-Tax Court di Pengadilan Pajak Indonesia - Agus Munandar; Aisya Sheilla Farina Nadia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The implementation of the e-Tax Court system in the Indonesian Tax Court is an innovative step in resolving tax disputes as intented by the Tax Court Law, namely resolving tax disputes in a fast, easy and efficient manner, however based on data obtained until August 2024 there were only 37.04% of disputes submitted through this system. This shows that the adoption rate is still relatively low. This research aims to determine the appropriate e-Tax Court implementation strategy by analyzing the strengths, weaknesses, opportunities and threats (SWOT) of this system. The method used is qualitative analysis through literature study. The analysis results show that the e-Tax Court has strengths in terms of saving time, costs, accessibility and transparency, but on the other hand it still has weaknesses in terms of technical and network infrastructure. Opportunities in terms of improving the credibility image of tax justice institutions and developing sustainable innovation are still wide open, however, there are threats in the form of resistance to change and data security risks due to the use of this system.